Policy Implementation of Stunting Prevention in Solok Selatan Regency - Elsa Wulan Suci; Rahmadani Yusran; M Fachri Adnan; Zikri Alhadi (Science and Environmental Journal for Postgraduate, 2023)
This study aims to analyze the implementation of stunting prevention policies in Solok Selatan Regency. This study uses a descriptive qualitative approach with primary and secondary data. This research was carried out in Solok Selatan Regency, to be precise, in all Regional Apparatus Organizations (OPDs) involved in preventing malnutrition. Data collection techniques were carried out through interviews and documentation. The results of the study show that stunting prevention policies are implemented by all OPDs based on their authority. However, this policy has not succeeded in realizing the achievement of policy objectives. This is due to economic, and educational factors, low communication and cooperation between OPDs, and the absence of system development by the regional government. This study concludes that local governments need to formulate local policies that can boost the people's economy. In the educational aspect, innovation programs to increase specific knowledge about quality nutritional intake are needed which can be developed by utilizing available natural resources. Meanwhile, in the bureaucratic aspect, it is necessary to increase the joint commitment of OPDs and open bureaucratic resources between OPDs to implement stunting prevention policies.